Data Dredging or Legitimate Research Method? Historiography and Its Potential for Management Research - Goodman, Robert S.; Kruger, Evonne Jonas (Academy of Management Review, 1988)
Robert S. Goodman, Evonne Jonas Kruger, Data Dredging or Legitimate Research Method? Historiography and Its Potential for Management Research, The Academy of Management Review, Vol. 13, No. 2 (Apr., 1988), pp. 315-325